Tyrosine Phosphorylation of CD2AP Affects Stability of the Slit Diaphragm Complex - Tossidou, Irini; Teng, Beina; Worthmann, Kirstin; Müller-Deile, Janina; Jobst-Schwan, Tilman; Kardinal, Christian; Schroder, Patricia; Bolanos-Palmieri, Patricia; Haller, Hermann; Willerding, Jonas; Drost, Dana M.; de Jonge, Laura; et al. (Journal of the American Society of Nephrology, 2019)
BACKGROUND: CD2-associated protein (CD2AP), a slit diaphragm-associated scaffolding protein involved in survival and regulation of the cytoskeleton in podocytes, is considered a "stabilizer" of the slit diaphragm complex that connects the slit diaphragm protein nephrin to the cytoskeleton of the cell. Tyrosine phosphorylation of slit diaphragm molecules can influence their surface expression, but it is unknown whether tyrosine phosphorylation events of CD2AP are also physiologically relevant to slit diaphragm stability. METHODS: We used isoelectric focusing, western blot analysis, and immunofluorescence to investigate phosphorylation of CD2AP, and phospho-CD2AP antibodies and site-directed mutagenesis to define the specific phosphorylated tyrosine residues. We used cross-species rescue experiments in Cd2apKD zebrafish and in Drosophila cindrRNAi mutants to define the physiologic relevance of CD2AP phosphorylation of the tyrosine residues. RESULTS: We found that VEGF-A stimulation can induce a tyrosine phosphorylation response in CD2AP in podocytes, and that these phosphorylation events have an important effect on slit diaphragm protein localization and functionality in vivo. We demonstrated that tyrosine in position Y10 of the SH3-1 domain of CD2AP is indispensable for CD2AP function in vivo. We found that the binding affinity of nephrin to CD2AP is significantly enhanced in the absence of Y10; however, unexpectedly, this increased affinity leads not to stabilization but to functional impairment of the glomerular filtration barrier. CONCLUSIONS: Our findings provide insight into CD2AP and its phosphorylation in the context of slit diaphragm functionality, and indicate a fine-tuned affinity balance of CD2AP and nephrin that is influenced by receptor tyrosine kinase stimulation.
CRIS-Team Scopus Importer:2019-07-26
Keywords: CD2AP; nephrin; Phosphorylation; podocyte